2017
DOI: 10.1021/acscatal.7b03198
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Cobalt Vanadium Oxide as a Highly Active Electrocatalyst for Oxygen Evolution

Abstract: The water-splitting reaction provides a promising mechanism to store renewable energies in the form of hydrogen fuel. The oxidation half-reaction, the oxygen evolution reaction (OER), is a complex four-electron process that constitutes an efficiency bottleneck in water splitting. Here we report a highly active OER catalyst, cobalt vanadium oxide. The catalyst is designed on the basis of a volcano plot of metal–OH bond strength and activity. The catalyst can be synthesized by a facile hydrothermal route. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
168
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(172 citation statements)
references
References 32 publications
4
168
0
Order By: Relevance
“…Only V 3+ was reserved after OER (Figure S4, Supporting Information), which indicated that V 4+ and V 5+ could be dissolved in alkaline solution . For anion, the O 1s XPS spectrum shown in Figure d can be divided into three peaks which locate at 531.8, 530.6, and 530.1 eV, corresponding to H 2 O, OH − , and O 2− , respectively …”
Section: Resultsmentioning
confidence: 99%
“…Only V 3+ was reserved after OER (Figure S4, Supporting Information), which indicated that V 4+ and V 5+ could be dissolved in alkaline solution . For anion, the O 1s XPS spectrum shown in Figure d can be divided into three peaks which locate at 531.8, 530.6, and 530.1 eV, corresponding to H 2 O, OH − , and O 2− , respectively …”
Section: Resultsmentioning
confidence: 99%
“…For example, Jaramillo's group developed Ce‐doped NiO x on Au substrate and found that Ce and Au affect the electronic structure of active Ni sites and facilitate the OER process on NiO x . Noting that the foreign metallic atom doping can balance the absorption and desorption energies for the intermediate species, amorphous CoVO x catalysts were prepared with rational bond energies . Fe‐doped VOOH hollow spheres were also synthesized by Sun's group following the similar principle .…”
Section: Nonprecious‐metal‐based Catalystsmentioning
confidence: 99%
“…Plenty of studies have reported that transition metal-based oxides and (oxy)hydroxides were used for their superior electrochemical performances in sodium ion batteries, [21][22][23] supercapacitors, [24][25][26] and electrocatalytic water splitting. [27][28][29][30][31][32][33] Particularly, iron (Fe)-based materials, known for their low-cost, earth-abundant and environmentally friendly characteristics, are widely used in water oxidation as electrocatalysts. [34][35][36] For example, Lou et al reported a self-templated method to improve the catalytic properties of the hydroxide in OER by obtaining ultrathin NiÀ Fe layered double hydroxide nanosheets which was composed of the hierarchical hollow nanoprisms.…”
Section: Introductionmentioning
confidence: 99%